Polymer-nano composite pour point depressant and preparation method thereof

Through the surface modification of MXENE and mixing with a polymer lowering agent to form a polymer-nano-compound coagulant, the problem of low existing coagulant efficiency is solved, significantly improved the liquidity of crude oil at low temperature conditions at low temperature conditions And lowering effect.

CN119371739AActive Publication Date: 2025-01-28YANSHAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411491886.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing pure polymer decoagulant is relatively low in efficiency, making it difficult to effectively reduce the freezing point of crude oil under low temperature conditions, resulting in the risk of safety accidents such as reduced liquidity and pipeline blockage.

Method used

Mixenne modified by MXENE was used to form a GMXENE using the hexane triaxyxilane, and the solution was mixed with the altosol-ethyl acetate-alcohol cluster lowering agent to form a polymer-nano composite coagulant. The shape of the bionic "brick mud" structure is formed to enhance the effect of lowering coagulation.

Benefits of technology

It significantly improves the liquidity and reducing effect of crude oil under low temperature conditions, reduces the ability of wax crystal to form a three -dimensional mesh gel structure, releases the restrained liquid oil, and reduces the viscosity of crude oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371739A_ABST
    Figure CN119371739A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer-nano composite pour point depressant and a preparation method thereof. The method comprises the following steps: carrying out surface modification on MXene by using hexadecyl trimethoxy silane to obtain GMXene; gMXene and a polymer pour point depressant are subjected to solution blending, and the polymer-nano composite pour point depressant is obtained. According to the invention, hexadecyl trimethoxysilane is adopted to carry out surface modification on MXene, silicon-oxygen bonds are formed on the surface of MXene, and through a bridging effect between a polymer and a crude oil interface, the adsorbability of crude oil and the dispersity of the pour point depressant in the crude oil are improved. After the modified MXene is used for carrying out surface modification on the ethylene-vinyl acetate copolymer pour point depressant, a bionic'brick mud 'structure is formed by utilizing a layered structure of the MXene, so that wax crystals separated out from crude oil are large and compact, the occupied space is reduced, the capability of forming a three-dimensional network gel structure by the wax crystals is effectively weakened, and the pour point depressing effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pour point depressants, and in particular to a preparation method of a polymer-nano composite pour point depressant. Background Art

[0002] During the pipeline transportation of crude oil, as the oil temperature decreases, wax crystals in the crude oil continue to precipitate and gradually aggregate to form a three-dimensional mesh gel structure, which reduces fluidity and reduces the effective pipeline diameter, which may cause safety accidents such as pipeline blockage and pipe condensation. Therefore, in the oil industry, it is extremely important to reduce the pour point of crude oil and improve its low-temperature fluidity. Adding pour point depressants is recognized as one of the most effective ways to ensure the safety of crude oil transportation due to its low cost and high efficiency.

[0003] Currently, the commonly used pure polymer depressants have low efficiency, while the nanomaterial MXene has excellent mechanical strength, thermal conductivity, low weight, high surface area and structural stability. It can be combined with polymers to enhance performance, and can be modified and grafted to produce the expected physical and chemical properties. Due to its unique multilayer structure and excellent physical and chemical properties, it has become one of the ideal candidate materials for constructing bionic "brick and mud" structures. Therefore, the study of efficient depressants for low-temperature transportation of high-freezing crude oil has become an urgent problem to be solved. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a polymer-nano composite pour point depressant and a preparation method thereof.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In one aspect, the present invention provides a method for preparing a polymer-nano composite pour point depressant, comprising the following steps:

[0007] (1) Surface modification of MXene using hexadecyltrimethoxysilane to obtain GMXene;

[0008] (2) The GMXene obtained in step (1) is solution blended with a polymer pour point depressant to obtain the polymer-nano composite pour point depressant.

[0009] As a preferred embodiment, in step (1), the MXene is prepared by a liquid phase exfoliation method;

[0010] Preferably, the liquid phase stripping method comprises the following steps: stirring the MAX phase Ti3AlC2 powder in an etchant at 30-50°C and 1000-1500 rpm for 12-24 hours;

[0011] Preferably, the etchant is a hydrofluoric acid solution;

[0012] Preferably, post-treatments including centrifugation, washing, filtration and drying are also included.

[0013] As a preferred embodiment, in step (1), the surface modification comprises the following steps:

[0014] The surface modification was completed by stirring MXene and hexadecyltrimethoxysilane in a solution;

[0015] Preferably, the stirring reaction temperature is 60-70°C;

[0016] Preferably, the stirring reaction time is 3.5 to 4.5 hours;

[0017] Preferably, the mass ratio of the MXene to hexadecyltrimethoxysilane is 1:0.5-1;

[0018] Preferably, the solution is a methanol-water solution;

[0019] In certain specific embodiments, post-treatments including centrifugation, filtration, drying and grinding are also included.

[0020] As a preferred embodiment, in step (2), the temperature of the solution blending is 60 to 80°C;

[0021] Preferably, the solution blending time is 3 to 5 hours;

[0022] Preferably, the reaction solvent of the solution blend is xylene;

[0023] Preferably, the solution blending is carried out in an inert atmosphere;

[0024] Preferably, the method further comprises the steps of precipitating the product of the solution blending method with a poor solvent, and obtaining the polymer-nano composite pour point depressant by suction filtration and drying;

[0025] Preferably, the poor solvent is methanol;

[0026] Preferably, the drying is carried out at 30-50° C. for 12-24 hours.

[0027] As a preferred embodiment, in step (2), the polymer pour point depressant is an ethylene-vinyl acetate copolymer pour point depressant;

[0028] Preferably, the mass ratio of the ethylene-vinyl acetate copolymer pour point depressant to the Mxene is 5:1-5.

[0029] In another aspect, the present invention provides a polymer-nano composite pour point depressant obtained by the above preparation method.

[0030] In yet another aspect, the present invention provides use of the polymer-nano composite pour point depressant in preparing a crude oil pour point depressant.

[0031] Preferably, the content of the polymer-nano composite pour point depressant in crude oil is 400-1200 ppm, preferably 400-800 ppm.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention uses hexadecyltrimethoxysilane to modify the surface of MXene, forming silicon-oxygen bonds on the surface of the two-dimensional material MXene, which can form a bridging effect at the interface between the polymer and crude oil, thereby improving the adsorption of crude oil and the dispersibility of the pour point depressant in crude oil.

[0034] (2) The present invention blends MXene surface-modified with hexadecyltrimethoxysilane with ethylene-vinyl acetate copolymer pour point depressant in a solution, performs surface modification on the pour point depressant, and utilizes the layered structure of MXene to form a bionic "brick-mud" structure, so that the wax crystals precipitated from the crude oil are large and dense, reducing the space occupied, effectively weakening the ability of the wax crystals to form a three-dimensional network gel structure, releasing the bound liquid oil, and improving the pour point depressant effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The figure is a flow chart for preparing the polymer-nano composite pour point depressant in Example 1 of the present invention.

[0036] Figure 2 FTIR spectra of MXene, GMXene, EVA and EVA-GMX (5:2) in Example 1 of the present invention.

[0037] Figure 3 This is a graph showing the water contact angle test results of MXene and GMXene in Example 1 of the present invention.

[0038] Figure 4 This is a graph showing the freezing point test results of crude oils with added EVA, EVA-GMX (5:1), and EVA-GMX (5:2) in Example 1 of the present invention.

[0039] Figure 5a Viscosity-temperature curves of crude oil with different concentrations of EVA-GMX (5:1) added; Figure 5b Viscosity-temperature curves of crude oil with different concentrations of EVA-GMX (5:2) added; Figure 5c Viscosity-temperature curve of crude oil without / doped with 800 ppm EVA / GMXene. DETAILED DESCRIPTION

[0040] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0041] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0042] Example 1

[0043] This embodiment provides a polymer-nano composite pour point depressant, and its preparation method is as follows Figure 1 As shown, the following steps are included:

[0044] (I) Preparation of Ti3AlC2

[0045] Step 1: Add 20 mL of 40% hydrofluoric acid solution into a polytetrafluoroethylene (100 mL) reaction kettle;

[0046] Step 2: Weigh 1g of MAX phase Ti3AlC2, add it into the reactor in small amounts, put it into an oil bath, and stir it with magnetic force at 1000rpm and 40℃ for 24h;

[0047] Step 3: Pour the obtained solution into a centrifuge tube, centrifuge at 5000 rpm for 5 min, add deionized water, and centrifuge for 5 to 6 times until the pH of the filtrate is neutral;

[0048] Step 4: Filter with a 0.22 μm water filter membrane, place the filtered product in a vacuum drying oven at 40 ° C for 2 hours, grind into powder, and obtain MXene phase Ti3AlC2;

[0049] (II) Surface modification of Ti3AlC2

[0050] Step 1: Prepare 100 mL of methanol-water solution (volume ratio is 9:1);

[0051] Step 2: Add 1 g of MXene phase Ti3AlC2 into methanol aqueous solution, disperse it by ultrasonic for 30 min and assist with mechanical stirring to form a uniform and stable dispersion;

[0052] Step 3: Add 1 mL of hexadecyltrimethoxysilane to the dispersion, put it in an oil bath, and stir it with a constant temperature magnetic stirrer at 1000 rpm and 70 °C for 3.5 h to promote the chemical bonding between the silane group and the MXene surface;

[0053] Step 4: centrifuge at 5000 rpm for 5 min, add deionized water, and centrifuge for 5 to 6 times; filter with filter paper, place in a vacuum drying oven at 40°C for 2 h, grind into powder, and obtain the modified product GMXene (abbreviated as GMX);

[0054] (III) Preparation of polymer-nano composite pour point depressant

[0055] Step 1: Add 40 mL of xylene into a flask, weigh 0.4 g, 0.8 g, and 2 g of GMXene into the flask, and ultrasonicate for 30 min to form a dispersion.

[0056] Step 2: Add 40 mL of xylene into a three-necked flask, weigh 2 g of ethylene-vinyl acetate copolymer pour point depressant (EVA, VA content is 25 wt.%) and add it into the flask, stir at 500 rpm and 70°C until it is completely dissolved in xylene;

[0057] Step 3: Under nitrogen atmosphere, slowly add the dispersion in step 1 to the solution in step 2, and react at 500 rpm and 70°C for 4 hours;

[0058] Step 4: Precipitate the mixed solution with excess methanol, filter the precipitate through filter paper, and dry it at 40 ° C for 12 h to obtain the final product EVA-GMX, which are EVA-GMX (5:1), EVA-GMX (5:2) and EVA-GMX (1:1)

[0059] Performance Testing

[0060] (1) The Fourier transform infrared spectra of MXene, GMXene, EVA and EVA-GMX (5:2) in Example 1 are shown in Figure 2 , as can be seen from the figure:

[0061] EVA-GMX formed by solution blending of EVA and GMXene has a new characteristic peak of 1136cm compared with pure EVA. -1 and 530cm -1 , which correspond to the Si-O-Si asymmetric stretching vibration of GMXene and the characteristic peak Ti-O stretching vibration of MXene, respectively, which indicates the presence of GMXene in the composite material and also shows that the Ti-O structure remains stable after blending treatment.

[0062] (2) The water contact angle test results of MXene and GMXene in Example 1 are shown in Figure 3 , where a1-a3 are MXene and b1-b6 are GMXene. It can be seen from the figure that:

[0063] Unmodified MXene quickly absorbs water and expands within 3 seconds after contact with water, indicating that it is hydrophilic (a1-a3). GMXene exhibits superhydrophobicity, and water droplets cannot adhere to its surface (b1-b5); the water contact angle of the GMXene surface is measured to be 153.58° (b6), indicating that the EVA-MXene nanocomposite pour point depressant can be evenly dispersed in crude oil, significantly reducing crude oil viscosity and improving flow properties.

[0064] (3) De-condensation effect test

[0065] Test Example 1: This test is aimed at high-pour point viscous oil containing wax and colloid asphaltene in a block of Shengli Oilfield. The pour point depressants prepared in Example 1 are used to compare and evaluate the pour point depressing effect (pour point). The evaluation standard is implemented in accordance with GB / T 26985-2018;

[0066] Test conditions: The pour point depressant dosage is 800 mg / L. The evaluation results are as follows: Figure 4 As shown;

[0067] Depend on Figure 4 It can be seen that the three pour point depressants provided in Example 1 have obvious pour point depressing effects on high pour point crude oil in a block of Shengli Oilfield, and a high pour point depressing effect can be achieved at a relatively low dosage.

[0068] Test Example 2: This test is aimed at high-viscosity viscous oil containing wax and colloid asphaltene in a block of Shengli Oilfield, and the pour point depressants prepared in Example 1 are used to conduct comparative evaluation of rheological properties (viscosity-temperature curve).

[0069] Test conditions: Crude oil samples without and with pour point depressants were preheated at 60°C for 30 min and cooled at a fixed rate of 0.5°C / min. The evaluation results are shown in the attached figure. Figure 5a-5c As shown:

[0070] When the addition amount of the three pour point depressants provided in Example 1 is 800ppm, the viscosity of the crude oil at 10°C is reduced to 12.4Pa·s and 11.4Pa·s, respectively, which is 47.2% and 51.5% lower than that of the crude oil without the pour point depressant. When the addition amount is increased to 1200ppm, the viscosity of the crude oil increases abnormally because the excess pour point depressant does not combine with the wax crystals and is suspended in the crude oil, causing a self-gelling effect and increasing the viscosity. The experimental results show that the EVA-GMX composite material can significantly improve the low-temperature fluidity and rheology of crude oil.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a polymer-nano composite pour point depressant, characterized in that: The following steps are involved: (1) Surface modification of MXene using hexadecyltrimethoxysilane to obtain GMXene; (2) The GMXene obtained in step (1) is solution blended with a polymer pour point depressant to obtain the polymer-nano composite pour point depressant.

2. The preparation method according to claim 1, characterized in that: In step (1), the MXene is prepared by a liquid phase exfoliation method.

3. The preparation method according to claim 2, characterized in that: The liquid phase stripping method comprises the following steps: stirring MAX phase Ti3AlC2 powder in an etchant at 30-50°C and 1000-1500 rpm for 12-24 hours; Preferably, the etchant is a hydrofluoric acid solution; Preferably, post-treatments including centrifugation, washing, filtration and drying are also included.

4. The preparation method according to claim 1, characterized in that: In step (1), the surface modification comprises the following steps: The surface modification was completed by stirring MXene and hexadecyltrimethoxysilane in a solution; Preferably, the stirring reaction temperature is 60-70°C; Preferably, the stirring reaction time is 3.5 to 4.5 hours; Preferably, the mass ratio of the MXene to hexadecyltrimethoxysilane is 1:0.5-1; Preferably, the solution is a methanol-water solution.

5. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the solution blending is 60 to 80° C.; Preferably, the solution blending time is 3 to 5 hours; Preferably, the reaction solvent of the solution blend is xylene; Preferably, the solution blending is performed in an inert atmosphere.

6. The preparation method according to claim 1, characterized in that: The method further comprises the steps of precipitating the product of the solution blending method in step (2) with a poor solvent, and obtaining a polymer-nano composite pour point depressant by suction filtration and drying; Preferably, the poor solvent is methanol; Preferably, the drying is carried out at 30-50° C. for 12-24 hours.

7. The preparation method according to claim 1, characterized in that: In step (2), the polymer pour point depressant is an ethylene-vinyl acetate copolymer pour point depressant; Preferably, the mass ratio of the ethylene-vinyl acetate copolymer pour point depressant to the Mxene is 5:1-5.

8. The polymer-nano composite pour point depressant obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the polymer-nano composite pour point depressant according to claim 8 in the preparation of a crude oil pour point depressant.

10. The use according to claim 9, characterized in that: The content of the polymer-nano composite pour point depressant in crude oil is 400-1200 ppm, preferably 400-800 ppm.

Citation Information

Patent Citations

  • MXene / conductive polymer composite aerogel and preparation method thereof

    CN108530889A

  • Preparation method of MXene-based efficient oil-water separation sponge

    CN110833708A

  • Mxene / ethylene-vinyl acetate copolymer flexible sensing material and preparation method thereof

    CN112175275A

  • Preparation method of nano composite pour point depressant

    CN113402724A

  • Method for extracting cobalt from disposed cathode material of secondary battery using mixed solvent

    KR1020230132940A